Hospital advertising: the Influence of perceptual and demographic factors on consumer dispositions - Andaleeb, Syed Saad (© 1994 MCB UP Limited, 2016)
This article was published in the Journal of Services Marketing [© 1994 MCB UP Limited ] and the definite version is available at : http://dx.doi.org/10.1108/08876049410053302 The Journal's website is at: http://www.emeraldinsight.com/doi/pdfplus/10.1108/08876049410053302